Health Protocol in Penataran Train during the COVID-19 Pandemic - Firmansyah, Nur Aldi; Wicaksono, Achmad; Anwar, M Ruslin (Civil and Environmental Science Journal (CIVENSE), 2021)
Penataran train decreased the number of passengers by 77.13% in April 2020, which resulted in a reduction in travel frequency and change origin-destination during the COVID-19 pandemic. This study aims to determine the characteristics of the Penataran train passengers and obtain policy recommendations about service standards and travel requirements based on respondents' choices using descriptive statistics. Questionnaires were distributed to 417 Penataran train passengers during new adaptation period. This study indicates that the frequency of trips during the new adaptation period is lower than before the pandemic. Only 10.55% of respondents give the reason that the risk of transmitting COVID-19 on the Penataran train is lower than other transportation. The maximum seating capacity is reduced to 50% according to respondent's perceptions. Wearing a mask, keep a distance, and wearing long-sleeved clothing can still be carried out because they are considered necessary as requirements for passenger travel. The GeNose C19 test letter is not recommended to be used as a document requirement because most respondents with low income do not want additional costs.